1940
DOI: 10.1098/rspb.1940.0041
|View full text |Cite
|
Sign up to set email alerts
|

X -ray studies of the molecular structure of myosin

Abstract: [P lates [15][16][17] The X -ra y an d elastic properties of m yosin are found to resem ble m ost closely, n o t those of n a tu ra l k eratin , b u t those of k e ra tin th a t has suffered breakdow n am ong th e cross-linkages (including disulphide bridges) of th e polypeptide grid. The su p erco n tractio n of m yosin cannot be explained as due sim ply to d isorientation of long th in u n its : it m u st involve a fu rth er folding of th e polypeptide chain system . The fact th a t m yosin an d k eratin are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1942
1942
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Early work on muscles was inspired by experience with humanbuilt machinery. Before the sliding filament hypoth esis, muscle was believed to work by the coiling of springlike proteins [17]. The tilting crossbridge idea of Hugh Huxley was also quite mechanical and, while physiologically correct, did not clearly explain how energy was transduced from chemical to mechanical form.…”
Section: A Very Brief Prehistory Of Molecular Machinesmentioning
confidence: 99%
“…Early work on muscles was inspired by experience with humanbuilt machinery. Before the sliding filament hypoth esis, muscle was believed to work by the coiling of springlike proteins [17]. The tilting crossbridge idea of Hugh Huxley was also quite mechanical and, while physiologically correct, did not clearly explain how energy was transduced from chemical to mechanical form.…”
Section: A Very Brief Prehistory Of Molecular Machinesmentioning
confidence: 99%
“…Early work showed that the sliding filament hypothesis (which was proposed on the basis of work in striated muscle) applied to molluscan smooth muscles as well (Dörr and Portzehl, 1954;Hanson and Lowy, 1959;Razumova et al, 1970;Millman and Elliott, 1972;Sugi and Tsuchiya, 1975). Molluscan muscle was also a preparation used in the extremely early X-ray diffraction studies of helical proteins (Astbury and Dickinson, 1940;Astbury, 1946;Fraser et al, 1965). X-ray reflections arising from the thin and thick filaments in these muscles are very well separated .…”
Section: 32mentioning
confidence: 99%